2014
DOI: 10.1128/ec.00109-14
|View full text |Cite
|
Sign up to set email alerts
|

A Ric8/Synembryn Homolog Promotes Gpa1 and Gpa2 Activation To Respectively Regulate Cyclic AMP and Pheromone Signaling in Cryptococcus neoformans

Abstract: The G protein ␣ subunits Gpa1, Gpa2, and Gpa3 mediate signal transduction and are important in the growth and virulence of Cryptococcus neoformans. To understand how Gpa1 functions without a conventional G␤ subunit, we characterized a resistance to inhibitors of cholinesterase 8 (Ric8) homolog from C. neoformans, which shares amino acid sequence homology with other Ric8 proteins that exhibit guanine nucleotide exchange factor (GEF) activity toward G␣. We found that the ric8 mutant was reduced in capsule size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 42 publications
4
23
0
Order By: Relevance
“…1). Ric8 also interacts with the Gα protein Gpa2 that has a role in pheromone signaling and this is consistent with the ric8 Δ mutant phenotype of reduced mating (Gong et al ., 2014). In C. neoformans , pheromone exchange between mating partners activates the Gα protein Gpa2 by dissociating it from a Gβγ complex.…”
Section: Association Of Rack1-like Proteins With the Camp/pka Pathwaysupporting
confidence: 77%
See 2 more Smart Citations
“…1). Ric8 also interacts with the Gα protein Gpa2 that has a role in pheromone signaling and this is consistent with the ric8 Δ mutant phenotype of reduced mating (Gong et al ., 2014). In C. neoformans , pheromone exchange between mating partners activates the Gα protein Gpa2 by dissociating it from a Gβγ complex.…”
Section: Association Of Rack1-like Proteins With the Camp/pka Pathwaysupporting
confidence: 77%
“…(2014) reported that the Ric8 protein (resistance to inhibitors of cholinesterase 8) is also involved in the cAMP/PKA pathway and pheromone signaling during mating in C. neoformans (Gong et al ., 2014). Ric8 functions as a guanine nucleotide exchange factor (GEF) for activation of Gα (Gpa1) in the cAMP/PKA pathway and deletion of RIC8 results in capsule and melanin defects similar to those of the gpa1 Δ mutant.…”
Section: Association Of Rack1-like Proteins With the Camp/pka Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The avirulence of mutants deficient in cAMP signal transduction has precluded direct testing of this model [20,28,29]. We therefore examined the influence of GPA1, CAC1, and PKA1, as well as RIC8, a Gα Guanine Nucleotide Exchange Factor (GEF) for Gpa1, on in vitro Titanisation [30]. Strains deficient in each of these genes failed to generate large cells in our assay ( Fig.…”
Section: The Camp Pathway Positively Regulates In Vitro Titanisationmentioning
confidence: 99%
“…The gpr4Δ gpr5Δ [42] was kindly provided by Joseph Heitman, Duke University, NC, USA. Strains ric8Δ and usv101Δ were obtained from the Madhani 2015 collection (NIH funding, R01AI100272) from the Fungal Genetics Stock Centre and were validated by PCR and shown to phenotypically match published strains [30,31]. C. gattii R265 [43] was provided by Neil Gow, University of Aberdeen, UK.…”
Section: Media and Strainsmentioning
confidence: 99%